Impact of primary posterior capsulorhexis on regeneratory after‐cataract and YAG laser rates with an acrylic micro‐incision intraocular lens with plate haptics: 1‐year and 3‐year results. Issue 8 (13th June 2019) - Menapace, Rupert; Schriefl, Sabine; Lwowski, Christoph; Leydolt, Christina
Abstract: Purpose: To evaluate the posterior capsule opacification (PCO) and YAG laser capsulotomy (YAG‐LCT) rates with a plate‐haptic acrylic micro‐incision intraocular lens (IOL) and the impact of primary posterior capsulorhexis. Methods: A total of 97 patients scheduled for immediate sequential bilateral cataract surgery underwent a randomized, prospective intraindividual comparison with the ZEISS Asphina 409MV plate‐haptic acrylic IOL with the eyes receiving an additional primary posterior capsulorhexis (PPCR) or not. YAG‐LCT and PCO rates were evaluated at 1 and 3 years. Three‐year PCO rates were calculated with a 3‐scenario method for eyes that underwent YAG‐LCT between 1 and 3 years. Results: A total of 56 patients were seen at 1 year, and 57 at 3 years. For the eyes without and with PPCR, YAG‐LCT rates were 14.3% and 0% at 1 year, and 59.7% and 3.5% at 3 years, respectively. Opacification rates at 1 year were 0.55 ± 0.99 and 0.05 ± 0.21 for the central 2‐mm optic zone. A total of 42 patients completed both the 1‐ and 3‐year follow‐up. Three‐year opacification rates for the group without PPCR were 1.99 ± 2.20, 2.26 ± 2.66 and 3.66 ± 3.61 for the central 2‐mm zone and 2.57 ± 2.07, 3.13 ± 3.03 and 4.09 ± 3.34 for the 4.5‐mm zone for the best, extrapolated and worst‐case scenarios, respectively. Conclusion: The ZEISS Asphina 409MV plate‐haptic acrylic IOL exhibited unusually high YAG‐LCT and PCO rates with standard in‐the‐bag implantation. PPCR was safe and effective in preventing central opacification and the need for YAG laser treatment.